The Role of Halal Awareness in Purchase Behavior Management: Evidence from Indonesian Higher Education - Didi Sutardi; Fatrilia Rasyi Radita; Ahmad Fauji; Sri Wahyuni; Masduki Asbari (International Journal of Management and Economic Research (IJOMER), 2025)
This research investigates the influence of attitude, subjective norms, and perceived behavioral control on the purchase behavior of working students in a private higher education institution in Tangerang. The study also examines the mediating role of purchase intention and the moderating effect of halal awareness. Using a simple random sampling technique, data were collected from a population of 410 working students, yielding 211 valid responses. Structural Equation Modeling (SEM) with SmartPLS 3.0 was employed for data analysis. Findings reveal that attitude, subjective norms, and perceived behavioral control significantly impact purchase intention, which in turn influences purchase behavior. Additionally, halal awareness moderates the relationship between purchase intention and purchase behavior. These results highlight the importance of halal awareness in shaping consumer purchasing decisions, particularly among working students.